China Intracranial Aneurysm Project (CIAP): protocol for a prospective cohort study of interventional treatment and craniotomy for unruptured aneurysms. Issue 5 (24th May 2018) - Chen, Yunchang; Fan, Haiyan; He, Xuying; Guo, Shenquan; Li, Xifeng; He, Min; Qu, Yan; Yang, Xinjian; Zhang, Hongqi; Sun, Xiaochuan; Wang, Liqun; Wang, Zhong; et al.
Abstract : Introduction: There are two approaches for the treatment of intracranial aneurysm (IA): interventional therapy and craniotomy, both of which have their advantages and disadvantages in terms of treatment efficacy. To avoid overtreatment of unruptured aneurysms (UIA), to save valuable medical resources and to reduce patient mortality and disability rate, it is vital that neurosurgeons select the most appropriate type of treatment to provide the best levels of care. In this study, we propose a refined, prospective, multicentre study for the Chinese population with strictly defined patient inclusion criteria, along with the selection of representative clinical participating centres. Methods and analysis: This report describes a multicentre, prospective cohort study. As IA is extremely harmful if it ruptures, ethical issues need to be taken into account with regard to this study. Researchers are therefore not able to use randomised controlled trials. The study will be conducted by 12 clinical centres located in different regions of China. The trial recruitment programme begins in 2016 and is scheduled to be completed in 2020. We expect 1500 participants with UIA to be included. Clinical information relating to the participants will be recorded objectively. The primary endpoints are an evaluation of the safety and efficiency of interventional treatment and craniotomy for 6 months after surgery, with each participant completing at least 1 year of follow-up. The secondary endpoint is the evaluation of safety and efficacy of interventional therapy and craniotomy clipping when participants are treated for 12 months. We also address the success of treatment and the incidence of adverse events. Ethics and dissemination: The research protocol and the informed consent form for participants in this study were approved by the Ethics Committee of Zhujiang Hospital of Southern Medical University (2017-SJWK-001). The results of this study are expected to be disseminated in peer-reviewed journals in 2021. Trial registration number: NCT03133598 .